POLA PEMBINAAN DAN PENGEMBANGAN AGAMA DI KABUPATEN KAMPAR - Agustiar Agustiar (An-Nida', 2011)
Construction and development of religion is one of the all important sector in system National Development Of Indonesia. made of " belief in God and fear to God which is Single The most " as first principality from nine national development principality in Outlines Bow State ( GBHN ) 1993 ago for example, is one of the evidence what a this state people look into religion as value system which very determine to realize national aspiration, prosperous and fair society. Statement of decanted politics in GBHN above beckoning to us that religion and construction of life believe in in Indonesia get especial priority in course of medial development of Indonesia society which is pluralistik. As part of society which is pluralistik, Sub-Province Camphor can be conceived of by part of deputizing Indonesia face in mini scale. This area is inhabited by some tribe exist in Indonesia and coloured by value system believe in from some of religion confessed officially in this state.